MANAGEMENT OF WATER POLLLUTED WITH BIOREMEDIATION - Edyson Indawan; KGS. Ahmadi (Bumi Lestari Journal of Environment)
The implication of those many human activities which longger progressively hencewill polluted. Tendency of damage of water effect of contaminantion more resulted fromapplied development practice not yet as according to methode and principle sustainabledevelopment.Bioremediation of technology at polluted water environment is aimed to destroy toxicand dangerous chemical compounds from disposal waste.